Pelatihan Pembuatan Sabun Ramah Lingkungan Berbasis Eco-Enzyme di Yayasan Amal Ikhlas Mandiri Tasikmalaya - Astuti, Pudji; Maulidya, Rahmi; Surjasa, Dadang; Amran, Tiena Gustina; Saraswati, Docki; Moengin, Parwadi; Sasongko, Agung; Habyba, Anik Nur; Sari, Indah Permata (Abdimas Universal, 2025)
Organic waste can decompose naturally, but organic waste also has the potential to damage the environment. Piles of organic waste that do not receive oxygen can produce dangerous methane gas. Piles of organic waste are a habitat for animals such as mice, flies, cockroaches, and mosquitoes. These animals carry infectious diseases through various bacteria and viruses. One way to reduce waste reaching final disposal sites is to process organic waste at the household level so that it has economic benefits and added value. The solution offered in this Community Service (PKM) is to process fresh organic waste, namely fresh vegetable waste and fresh fruit peels, and utilize the enzyme content of these organic materials through anaerobic fermentation, which produces coenzymes. The eco-enzyme produced is processed into a solid eco-enzyme soap derivative product. Apart from being used for household purposes, it can also be sold, increasing family income. Community service is carried out in collaboration with the Ikhlas Mandiri Charitable Foundation. The PKM was carried out in Pagerageung village, Tasikmalaya Regency. The results of the PkM showed that the participants felt capable of making eco-enzyme soap and were interested in making it in the future. Factors that support the sustainability of PKM activities are the availability of organic waste (fresh fruit and vegetable peels), coconut oil as a raw material for soap, and the support of the Yayasan Amal Ikhlas Mandiri.